Mechanisms of intersectoral interaction of political elites, state authorities and civil society in conditions of migration crisis - Nazarchuk, Oleksandr (Migration & Law, 2024)
The article is devoted to the study of the mechanisms of intersectoral interaction between political elites, state structures and civil society in Ukraine with an emphasis on solving problems in the migration sphere. In the context of contemporary political and social challenges, such as democratization, institutional reform, and decentralization of power, effective interaction between these sectors plays a crucial role in shaping policy decisions, integrating migrants, and protecting their rights. Analysis of the processes of intersectoral cooperation is important for increasing the transparency of state administration, strengthening citizens' trust in the authorities, and ensuring effective solutions to migration issues. As a result of the study, it was found that the effectiveness of intersectoral cooperation in Ukraine depends significantly on the transparency of political processes, the presence of an institutional framework for cooperation, as well as the active participation of civil society. Modern models of interaction, which include elements of social partnership and dialogue between the state, business and public organizations, contribute to more effective political decision-making. However, the study also identified a number of barriers, such as insufficient institutional support, weak communication between sectors and distrust of public authorities. The study emphasizes the need to improve mechanisms of intersectoral interaction through strengthening social dialogue, increasing institutional capacity and ensuring transparency of state processes. This, in turn, will strengthen citizens’ trust in the authorities and contribute to the further development of democratic institutions in Ukraine.
Keywords: Institutional interaction; Public control; Public administration; Social partnership; Political elites; Migration crisis